Barreras personales y ambientales para la práctica de actividad física en adultos mexicanos - Ceballos Gurrola, Oswaldo; Medina Rodríguez, Rosa Elena; Enríquez Reyna, María Cristina; Ceballos Medina, Oswaldo
The goal of this job it was to know the personal and social factors that act as barriers for the practice of healthy physical activities among Mexican adult population. Participated 601 subjects sample was used. A survey called “Physical activity and quality of life·” was applied. It has been proved the existence of a positive attitude of at elderly people, but it doesn’t correspond with its practice. Middle class population is more active than upper and low strata. Women do less physical activity than men and their tendency is to do it together (couple). The social activities as well as the lack of public spaces and insecurity, left little room for exercise. It was appreciated a poor sport culture, more in upper and lower strata. A profile of physical activity has been found by gender. The infrastructure and the social climate are considered barriers of engaging in physical activit.